Improving Islamic Education Learning Outcomes with Technology Integration Based on the TPACK Method at SD Negeri 21 Bonjol - Scorfiana, Asnoni (Jurnal Profesi Guru Indonesia, 2024)
This study aims to improve student learning outcomes in Islamic religious education learning using technology integration based on the TPACK Method. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that technology integration based on the TPACK Method can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 47.56%, the first cycle 65.47% and in the second cycle increased to 85.57%. Thus, the use of technology integration based on the TPACK Method can be used as an alternative to improve student learning outcomes in Islamic religious education learning.